2017
DOI: 10.1111/gcb.13647
|View full text |Cite
|
Sign up to set email alerts
|

Shifting paradigms in restoration of the world's coral reefs

Abstract: Many ecosystems around the world are rapidly deteriorating due to both local and global pressures, and perhaps none so precipitously as coral reefs. Management of coral reefs through maintenance (e.g., marine-protected areas, catchment management to improve water quality), restoration, as well as global and national governmental agreements to reduce greenhouse gas emissions (e.g., the 2015 Paris Agreement) is critical for the persistence of coral reefs. Despite these initiatives, the health and abundance of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
306
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 358 publications
(323 citation statements)
references
References 135 publications
(154 reference statements)
1
306
0
Order By: Relevance
“…Reduction of emissions, in particular carbon dioxide, is undoubtedly required to preserve the future form, function and ecosystem services of coral reefs (Gattuso et al, 2015;Hughes et al, 2017). But there is also an increasing debate over the need to facilitate coral survival through proactive reef management, e.g., reef restoration and/or assisted evolution processes (e.g., Coles and Riegl, 2013;van Oppen et al, 2015;Oppen et al, 2017). The use of proactive reef management is highly debated and beyond this synthesis (see van Oppen et al, 2015;Oppen et al, 2017), but what is evident from these extreme environments is the presence of corals that have traits highly favorable for future survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of emissions, in particular carbon dioxide, is undoubtedly required to preserve the future form, function and ecosystem services of coral reefs (Gattuso et al, 2015;Hughes et al, 2017). But there is also an increasing debate over the need to facilitate coral survival through proactive reef management, e.g., reef restoration and/or assisted evolution processes (e.g., Coles and Riegl, 2013;van Oppen et al, 2015;Oppen et al, 2017). The use of proactive reef management is highly debated and beyond this synthesis (see van Oppen et al, 2015;Oppen et al, 2017), but what is evident from these extreme environments is the presence of corals that have traits highly favorable for future survival.…”
Section: Resultsmentioning
confidence: 99%
“…But there is also an increasing debate over the need to facilitate coral survival through proactive reef management, e.g., reef restoration and/or assisted evolution processes (e.g., Coles and Riegl, 2013;van Oppen et al, 2015;Oppen et al, 2017). The use of proactive reef management is highly debated and beyond this synthesis (see van Oppen et al, 2015;Oppen et al, 2017), but what is evident from these extreme environments is the presence of corals that have traits highly favorable for future survival. For many environments we still do not know how these traits may be conserved or lost as corals are moved to new environments, however evidence of heritable heat-tolerance and conserved thermal tolerance (Hume et al, 2013) has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of such populations to serve as a source for adaptive genetic variation for surrounding habitats remains poorly explored. Potentially, these populations can provide adaptive alleles that could be harnessed in assisted gene flow or selective breeding initiatives that aim to increase climate resilience in the receiving populations (Hoegh‐Guldberg et al., ; van Oppen, Oliver, Putnam, & Gates, ; van Oppen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several observations of an increase in tolerance of coral bleaching after successive bleaching events suggest that adaptation and/or acclimatization are possible under certain conditions (Maynard et al, 2008;Berkelmans, 2009;Guest et al, 2012;Penin et al, 2013). Nevertheless, over 50% of the world's coral reefs has been lost in the last three decades, with the Caribbean having lost over 80% of its coral cover (50 Reefs, 2017) 1 , indicating that the rates of natural adaptation and acclimatization are overall insufficient to keep pace with the rate of environmental changes (van Oppen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An effective restoration strategy should thus incorporate an understanding of present day ecological characteristics of species, characteristics of future available habitats, and adaptive potential of species (Becker et al, 2013). The use of non-local and climate resilient materials is controversial, but is gaining traction in wildland restoration (Jones and Monaco, 2009), revegetation Breed et al, 2013), and coral reef restoration (Rau et al, 2012;van Oppen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%